Prematuridade e baixo peso em pré-escolares: fatores de risco ao desenvolvimento da linguagem e alterações fonológico-lexicais - Iemma, Elisa Pinhata (2010)
The expressive number of premature births shows the necessity of measures focused in preventing disorders in these children development. Literature reveals that language is one of the areas that may be affected when the child is exposed to risk factors. Considering language as the predictor of academic intelligence and skills, it becomes relevant to study the phonological and lexical aspects of preschool children with historical of prematurity and low birth weight. Supposedly, these children may present faults in this repertory in the moments that precede their formal schooling. This research received the approval of the Ethics Committee of the Federal University of São Carlos. It reports a descriptive study which aimed to detect language alterations/disorders in preterm born children with low weight which go to preschool. The following instruments were used to collect data: Critério de Classificação Econômica Brasil (2008); maternity house medical records, Screening Test Development Denver II (TSDD-II) and ABFW test. The participants in this study were 19 children between 3 and 5 years-old with historical of prematurity and low weight that required neonatal ICU after birth and are enrolled in the Public System of Child Education (Municipal Kindergarten). The results present, initially, the profile of the study sample with data from the children clinical history and their socio economic situation. The results yet reveal that in the Denver Test (TSDD-II), language was, among four other areas, the most affected. In this situation, 9 of the 19 children under evaluation have presented risk. Regarding the ABFW test performance, it is stressed that all the participants have presented risks. Regarding the phonological aspects, 8 children have presented an altered performance in the phonologic test. All the participants presented vocabulary deficiency. By analyzing language, 5 of the 19 children had faults in the phonologic areas of ABFW and of vocabulary, as well as the presence of risk in the language area in TSDD-II. The importance of the evaluation procedures and the language development accompaniment of this population in the moments that precede litaracy as preventive measures is being largely discussed, as well as the contributions of the ABFW test as an instrument that allows not only to situate the deficits but also, based on these deficits, to elaborate strategies of intervention for parents and teachers. The data related to clinical history and socio economic level were used to make interpretations of the similarities and differences in the scores found in both instruments from the concepts of risk, protection and resilience. The small number of participants can be pointed out as a limitating factor of this paper. For future studies it is suggested the conduct of follow-up and the development of intervention programs directed to parents and teachers in the perspective to prevent or minimize communicative deficits.